Managing Male And Female Athletes For Increased Sports Performance In Public Universities In Rivers State - Deemua, G. A. (Advances in Social Sciences Research Journal, 2020)
For any organistion to survive, it must depend on the good welfare package which such organization has for the staff and students inclusive. Managing student-athletes behaviours pre-requisite for increased sports performance at the university level. However, in recent times, university administrators have not been giving attention to properly managed and prepare their athletes for national and international competitives. These problems like inadequate funding, lack of facility and training equipment, poor training programmes, poor motivational techniques and, lack of incentives have been attributed to over management of athletes’ behaviour which has affected the performance of athletes. Parents, coaches and stakeholders in the sports industry need to play as stronger educational and supervisory role so that these young athletes will be able to acquire both physical and intellectual-skills which will enable them to live well and help in the development of the society.